Isolation and characterization of microplastics in marine foodstuff - Golieskardi, Abolfazl (2017)
Due to the persistence and ubiquity of plastic debris in the marine environment, these contaminants have become one of the major threats to the ecosystem. Disposed plastic debris may never degrade but instead breakdown to smaller particles, termed microplastic (MP). Microplastics have been previously detected in a wide array of organisms, however, MP loads in processed seafood products such as canned sardine and saltwater products such as commercial salt originating from various regions of the world has never been investigated. To extract MPs from organisms, an efficient digesting solution is required. In an attempt to select an optimum digesting solution, the efficiency of different oxidative agents (NaClO or H2O2), bases (NaOH or KOH), and acids [HCl or HNO3; concentrated and diluted (5%)] in digesting fish tissues at room temperature (RT, 25 °C), 40, 50, or 60 °C was assessed and those treatments that were efficient in digesting the biological materials (>95%) were evaluated for their compatibility with eight major plastic polymers (assessed through recovery rate, Raman spectroscopy analysis, and morphological changes). Following the selection of appropriate solution, the MP loads in 20 brands of canned sardine originating from 13 countries were assessed. In addition, the presence of MPs in 17 brands of commercial salts originating from 8 countries has been investigated. Among the tested solutions, NaClO, NaOH, and diluted acids did not efficiently digest the biological matrices. The H2O2treatment only at 50 °C resulted in satisfactory digestion efficiency, although it decreased the recovery rate of nylon-6 and nylon-66 and changed the colour of polyethylene terephthalate fragments. Concentrated HCl and HNO3 treatments at RT fully digested the fish tissues, but also had a destructive impact on most polymers, particularly nylon-6 and nylon-66. Potassium hydroxide solution was able to fully eliminate the biological matrices at all temperatures. However, at 50 and 60 °C, it reduced the recovery rate of polyethylene terephthalate and polyvinyl chloride, and changed the colour of nylon-66. According to our results, treating biological materials with 10% KOH solution and incubating at 40 °C was time and cost-effective, efficient in digesting biological materials, and had no impact on the integrity of the plastic polymers. Study on canned sardine has shown that plastic particles were absent in 16 brands while between 1 and 3 plastic particles per brand were found in the other 4 brands. Out of 21 extracted particles, 28.5% were plastic polymers, 42.8% were additives, 4.7% were non-plastic, and 23.8% were unidentified. The most abundant plastic polymers were polypropylene (33.3%) and polyethylene terephthalate (33.3%). The analysis of commercial salts for MP loads has revealed that MPs were absent in one brand while others contained between 1 and 10 MPs/Kg of salt. Out of the 72 extracted particles, 41.6% were plastic polymers, 23.6% were pigments, 5.50% were amorphous carbon, and 29.1% remained unidentified. The most common plastic polymers were polypropylene (40.0%) and polyethylene (33.3%). Although this study presents a low level of anthropogenic particles intake from the canned sardine (1 to 5 anthropogenic particles per individual per annum) and salts (maximum 37 particles per individual per annum) which warrants negligible health impacts on consumers, however, due to the progressive fragmentation of MPs in the environment, the number of MPs in these products tend to increase. As such, it is highly recommended that the quantification of MPs in foodstuffs to be included as one of the components of food safety management system.